Surface functionalization of WSe2 by F16CoPc. Issue 6 (27th December 2016) - Rückerl, Florian; Klaproth, Tom; Schuster, Roman; Büchner, Bernd; Knupfer, Martin
Abstract: We have investigated the electronic properties of WSe2 surfaces covered by fluorinated cobalt phthalocyanine (F16 CoPc) using photoemission spectroscopy. We show that a charge transfer occurs at this interface, which results in the creation of holes in the WSe2 surface while the Co center of the phthalocyanine is reduced to Co(I). We observe a potential change in WSe2 approaching the surface as a consequence of the induced positive charges near the surface. In addition, our data allow for a rough estimation of the induced charge density and suggest that the holes might be localized.